Peranan gambar dalam penulisan esei - Kasma Mohd Hayas; Sabariah Abd. Rahim; Alice Lim (2013)
Writing exercise is one of the important exercises in the learning of second or foreign language because it fortifies students’ writing skills. Writing helps students to improve spelling, apply different genres, use rules of grammar, and develop coherence, and unity of ideas, to name a few. However, many students are not really interested to write because they find writing difficult and not important. In this study, 40 students learning the Spanish and English Languages in Universiti Malaysia Sabah (UMS), were given two different writing tasks, i.e. free-writing and guided-writing, of similar topic. The purpose of this study is to evaluate the content, sentence structure, vocabulary and mechanics of the students’ essay writings (the useof transitions). Both tasks may have positive and negative roles that may result or cause by the nature of the tasks, i.e. free-writing---students are only provided with the topic, and guided-writing---students are provided with topic as well as additional information (pictures) as stimulants. Therefore, the paper discusses the negative and positive roles of the tasks. It is hoped that the findings of this study will benefit teachers of second or foreign languages on how to assist students to write better.